NETWORK WARS – MODERN WARS - Artemov, Volodymyr; Khoroshko, Volodymyr (Ukrainian Information Security Research Journal, 2024)
The article examines the theory of network-centric warfare and its impact on the present. It was developed in the second half of the twentieth century and is widely used in the wars of the twenty-first century. The essence of the concept of network-centric warfare can be redefined as follows: it is a war of the "blind" against the "sighted". The physical strength of the "blind man" is the combat strength of classical armed forces that do not take advantage of network-centric approaches, which does not guarantee an advantage in modern combat. This is a losing situation. Network-centric warfare consists of 3 lattice subsystems: information, sensor (i.e., intelligence) and combat. But its basis is the information subsystem, the goals of which, according to the concept, are the so-called Warden rings. Using the theory of network-centric warfare and hybrid warfare tactics, Russia seized Crimea and occupied Donbas. And on 24 February 2024, Russia launched a war against Ukraine, repeating its actions during the aggression against Georgia in 2008. That is, it started with cyberattacks on government agencies and government control centres. But the Russian Federation, using elements of network-centric warfare, is fighting as it did in World War II. Ukraine is making a transition from managing troops and weapons to managing armed struggle. Russia’s war against Ukraine shows that in modern warfare, the winner is the one who is quicker to perceive new technologies and implement them, adopts and implements new military doctrines and concepts that are in line with the spirit of the times and enable not only the use of new technologies and ideas, but also knows well which ones to use and when. High technologies are now turning into a systemic factor in modern armed struggle. They make it possible to reach that new stage in the development of military art - the transition from command and control of troops in the course of armed struggle to conflict management in general.